Sanitasi, infeksi, dan status gizi anak balita di Kecamatan Tenggarong Kabupaten Kutai Kartanegara - Andi Tenri Abeng; Djauhar Ismail; Emy Huriyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Malnutrition is a public health problem commonly encountered in developing countries. Almost 50% of 10-11 millions of mortality among children under-fives caused by malnutrition that is preventable. District of Kutai Kartanegara is known as the most wealth of district in Indonesia, yet the wealth cannot automatically solve the problem of its people. Numerous efforts have been made to solve malnutrition problem yet the morbidity rate is still relatively high.Objective: The study aimed to identify an association between sanitation with infection and nutritional status of under five at Subdistrict of Tenggarong, District of Kutai Kartanegara.Method: The study was observational with cross sectional design. Samples consisted of 187 under fives of 7-60 months taken using proportional random sampling technique. Variable of sanitation was obtained from the interview with subjects using questionnaire and direct observation. Variable of infection was obtained from an interview with subjects and cross check at health centers. The dependent variable of nutritional status was based on anthropometric assessment using weight/height index. The bivariate analysis used Chi-Square and multivariate analysis used logistic regression.Results: The result of the statistical test showed there was a significant association between sanitation and infection (acute respiratory tract infection/ARI, diarrhea) of under fives (p<0.05). There was an association between ARI and diarrhea with wasted children (p<0.05).Conclusion: There was the significant association between sanitation, infection and nutritional status of under five at Subdistrict of Tenggarong District of Kutai Kartanegara.